Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1103/physrevb.70.245425
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy of OH-functionalized single-wall carbon nanotubes

Abstract: The effects of the OH group on the electronic and optical properties of single-wall carbon nanotubes were investigated using first principles electronic structure calculations. Our results confirm band-gap reduction of semiconductor carbon nanotubes up on addition of the OH group. An additional energy level emerges near the Fermi level, which is due to coupling between one p orbital of the oxygen with the big bond of the nanotube. Analysis of loss function showed that the plasmon excitation shifts to lower fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 32 publications
(27 reference statements)
6
52
0
Order By: Relevance
“…This modeling method was rejected since the choice of capping/functional group has previously been shown to influence the molecular and electronic structures of SWNTs quite considerably. 83 Also, there exists the possibility of interactions between the capping/functional group and the KI crystal and the influence of these end effects on the energetic and structural data would be difficult to quantify and would undoubtedly depend on the chosen method for terminating the SWNT.…”
Section: A Ki@swnt: the Modelmentioning
confidence: 99%
“…This modeling method was rejected since the choice of capping/functional group has previously been shown to influence the molecular and electronic structures of SWNTs quite considerably. 83 Also, there exists the possibility of interactions between the capping/functional group and the KI crystal and the influence of these end effects on the energetic and structural data would be difficult to quantify and would undoubtedly depend on the chosen method for terminating the SWNT.…”
Section: A Ki@swnt: the Modelmentioning
confidence: 99%
“…This is because of the interaction between the oxygen and carbon atom. OH group can form an acceptor level and enhance the conductivity of the CNT [21]. The concentration of the OH group in the solution can be calculated by the pH value.…”
Section: Ph Measurement Using the Cnt-based Sensorsmentioning
confidence: 99%
“…Therefore, to solve this problems, a series of functionalization schemes has been recently proposed (36)(37)(38)(39). In particular, experimental work has shown that some metal nano particles-decorated CNTs display high sensitivity and fast response to gaseous molecules at room temperature (40)(41)(42)(43)(44)(45)(46)(47). For example, CNTs decorated with some transition metal such as Pd, Pt and Rh nanoparticle could be used for detection of H 2 (42)(43)(44)(45), CH 4 (44,46) and CO (44).…”
Section: Introductionmentioning
confidence: 99%